RELATION OF RETINOPATHY OF PREMATURITY WITH CHANGE IN BIRTH WEIGHT DURING THE POSTNATAL PERIOD IN PREMATURE INFANTS IN A TERTIARY CARE HOSPITAL IN LAHORE - CHAUHAN, K; SAIGOL, HK; RAUF, A; AHMAD, NI; HOTIANA, NA; AKBAR, S; ALI, F (Biological and Clinical Sciences Research Journal, 2023)
This study assessed the relationship between Retinopathy of Prematurity (ROP) and post-natal weight gain in premature infants admitted to the Neonatal Intensive Care Unit (NICU). The observational study was conducted in the Department of Ophthalmology in collaboration with the Department of Pediatrics, the neonatal intensive care unit (NICU) at Sir Ganga Ram hospital in Lahore from September 2020 to August 2022. Data including gender, Birth Weight (BW), Gestational Age (GA), and post-natal complications(hypotension, packed red cell transfusion, intraventricular hemorrhage, necrotizing enterocolitis, and respiratory distress syndrome) of all the premature infants with gestational age less than 35 weeks, admitted in NICU was collected. All these premature infants underwent eye examination for the presence or absence of ROP, and weight was measured. In the second, fourth, and sixth weeks, their relative weight gain(RWG) was calculated. Infants with ROP had lower BW (P <0.001) and GA (P<0.001). More infants with severe ROP had body weight <1000g and post-natal complications than those without ROP. Moreover, RWG at the 2nd and 4th weeks was lower in infants with ROP than with no ROP infants. Based on the result, it can be concluded that the ROP was associated with low postnatal weight gain, birth weight, and gestational age.